God and reason in the Middle Ages - Grant, Edward, 1926- (Cambridge [England] ; New York : Cambridge University Press, 2001)
"The object of this book is twofold: to describe how reason was manifested in the curriculum of medieval universities, especially in the subjects of logic, natural philosophy, and theology; and to explain how the Middle Ages acquired an undeserved reputation as an age of superstition, barbarism, and unreason."--BOOK JACKET.
1. The Emergence of a Transformed Europe in the Twelfth Century. Centuries of Dissolution: Europe at Its Nadir. The Gradual Evolution toward a New Europe. Reflections on the Role of Reason in the New Europe -- 2. Reason Asserts Itself: The Challenge to Authority in the Early Middle Ages to 1200. Christianity and Late Antiquity. Reason and Logic in the Twelfth Century. Theology. Natural Philosophy. Law -- 3. Reason Takes Hold: Aristotle and the Medieval University. The Latin Tradition of Learning in the Early Middle Ages prior to the Influx of New Translations. The Translations. Aristotle's Legacy to the Middle Ages. The Medieval University -- 4. Reason in Action: Logic in the Faculty of Arts. The Old and New Logic. Forms of Literature in Logic. The Sophism. Other Themes in Medieval Logic. The Impact of Logic in Medieval Europe -- 5. Reason in Action: Natural Philosophy in the Faculty of Arts. What Is Natural Philosophy? Natural Philosophy and the Exact Sciences. Doing Natural Philosophy: Nicole Oresme. Reason and the Senses in Natural Philosophy: Empiricism without Observation. Reason and Revelation: How Faith and Theology Affected Natural Philosophy -- 6. Reason in Action: Theology in the Faculty of Theology. The New Theology. God and the Infinite. Natural Philosophy in Theology -- 7. The Assault on the Middle Ages. The Medieval and Early Modern "Ages of Reason" The Onslaught against Scholasticism and the Middle Ages. Contemporary Attitudes toward "Medieval" and "Middle Ages" Redressing the Balance -- Conclusion: The Culture and Spirit of "Poking Around."
Includes bibliographical references (p. 365-383) and index.
Keywords: Reason -- History; Faith and reason -- Christianity -- History of doctrines; Learning and scholarship -- History -- Medieval, 500-1500.; Universities and colleges -- Europe -- History